End‐stage kidney disease in Fiji. Issue 4 (7th April 2019) - Krishnan, Amrish; Chandra, Yogeshni; Malani, Joji; Jesudason, Shilpanjali; Sen, Shaundeep; Ritchie, Angus G.
Abstract: Background: Chronic kidney disease is now a leading cause of death in Fiji. The country lacks even basic statistics about the incidence of end‐stage kidney disease (ESKD) and presents significant challenges to conducting clinical research. Aim: To estimate the incidence and characteristics of ESKD in Fijian adults. Methods: A retrospective cohort study was conducted of patients admitted to Colonial War Memorial Hospital in Suva, Fiji, in 2012. Suspected ESKD cases were identified from laboratory registers of renal function tests and confirmed through medical record review. Population data were from the Fijian Bureau of Statistics. Results: Screening identified 1474 suspected ESKD cases. Following removal of 763 duplicates and cases with discrepant identifiers, 711 unique cases remained. An additional 552 cases met exclusion criteria, including acute kidney injury (247), failure to be admitted (131) and pre‐existing ESKD diagnosis (103), leaving 159 cases of confirmed ESKD. Median age was 57 years (interquartile range 47–65). Crude and age‐adjusted ESKD incidence rates were 753 per million population (pmp) (95% confidence interval (CI) 636–870) and 793 pmp (95% CI 669–916), respectively, rising to 938 pmp (95% CI 804–1072) if African‐American correction was removed. Diabetic nephropathy was the most common cause of ESKD (65.4%). Conclusion: The incidence of ESKD in Fiji is high. This is a substantial public health problem that is likely impacting life expectancy and quality of life. Improving screening, detection and management of kidney disease should be given more prominence in programmes to address non‐communicable diseases in Fiji and the Western Pacific.